IMPLEMENTASI PROJECT BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR MATERI LARUTAN ELKTROLIT DAN NONELEKTROLIT - Putra, Reska Dastri Okta; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the lack of motivation and study achievements in electrolyte and non-electrolyte solution material in X class of Indonesia Muda Senior High School. The purpose of this study to determinate whether there a significant differencesof achievements and motivations between students before and after treatment through Project Based Learning (PjBL). To achieve them, a number of thirty students were asked to participate in the study. According to one group pre-test and post-test research design, the students were given a pretest, a posttest, and a questionnaire. As a set of data collection tools, pretest and posttest were used to measure achievement meanwhile questionnaire was used to measure motivations. Analysis data of pretest and posttest through paired sample T-test, and data of questionnaire through T-one sample test. Showed that P-value were 0,000 and 0,000 respectively. In conclusion, there a significant differencesat achievements and motivations before and after treatment used the Project Based Learning (PjBL).Keywords:Electrolyte and Non-Electrolyte Solutions, Motivation, Project Based Learning, Study Achievements